Evaluation of cane stillage in substitution of water in finishing feedlot. 2. Behaviour and metabolic profile - Arrigoni, Mário de Beni; Silveira, Antonio Carlos; Furlan, Luiz Roberto; Parré, Claudinei; Costa, Ciniro; Curi, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 1994)
Fifteen animals from Canchim group and fifteen from Nelore were observed in the following treatments: water (A), molasses soluble + magnesium oxide (V) and molasses soluble + magnesium oxide + sodium bicarbonate (V+B). They were observed during continuous 24 hours every 30 days up to 90 days periods. During the weighting, every 28 days blood samples were collected to determine metabolic outline. Treatments did not affect (P > 0.05) animal behaviour on metabolic and the obtained mean values were within the normal range. They were, respectively for Canchim and Nelore: Feeding 270 and 223 minutes; Rumination 374 and 356 minutes; Idleness 745 and 863 minutes; Glicose 86 and 88 mg/dl; Urea 10 and 23 mg/dl: Uric acid 1,3 and 1,2 mg/dl; Total protein 7,0 and 6,8 g/dl; Albumin 3,1 and 3,1 g/dl; Creatinin 1,5 and 1,6 mg/dl; Sodium 140 and 142 meq/dl; Potassium 4,2 and 4,3 meq/l and Calcium 10,0 and 9,8 mg/dl. It was concluded that molasses soluble as a substitute of water has not changed the ethologic parameters neither metabolic outline of both genetic group when in finishing feedlot.